Spatial Transcriptomics in Inflammatory Skin Diseases Using GeoMx Digital Spatial Profiling: A Practical Guide for Applications in Dermatology - Christina Cho; Nazgol-Sadat Haddadi; Michal Kidacki; Gavitt A. Woodard; Saeed Shakiba; Ümmügülsüm Yıldız-Altay; Jillian M. Richmond; Matthew D. Vesely (JID Innovations)
The spatial organization of the skin is critical for its function. In particular, the skin immune microenvironment is arranged spatially and temporally, such that imbalances in the immune milieu are indicative of disease. Spatial transcriptomic platforms are helping to provide additional insights into aberrant inflammation in tissues that are not captured by tissue processing required for single-cell RNA sequencing. In this paper, we discuss a technical and user experience overview of NanoString's GeoMx Digital Spatial Profiler to perform in-depth spatial analysis of the transcriptome in inflammatory skin diseases. Our objective is to provide potential pitfalls and methods to optimize RNA capture that are not readily available in the manufacturer’s guidelines. We use concrete examples from our experiments to demonstrate these strategies in inflammatory skin diseases, including psoriasis, lichen planus, and discoid lupus erythematosus. Overall, we hope to illustrate the potential of digital spatial profiling to dissect skin disease pathogenesis in a spatially resolved manner and provide a framework for other skin biology investigators using digital spatial profiling.